Maternal Goals for Childbirth Associated with Planned Vaginal and Planned Cesarean Birth - Quiroz, Lieschen H. (2011)
We describe maternal childbirth goals among women planning either cesarean or vaginal birth. Women in the third trimester planning cesarean or vaginal birth were asked to report up to five childbirth goals. Goal achievement was assessed postpartum. Based on free-text responses, discrete goal categories were identified. Goals and goal achievement were compared between the two groups. Satisfaction was rated on a visual analogue scale and was compared with goal achievement. The sample included 163 women planning vaginal birth and 69 women planning cesarean. Twelve goal categories were identified. Only women planning vaginal birth reported a desire to achieve fulfillment related to childbirth. Women planning cesarean were less likely to express a desire to maintain control over their own responses during childbirth and more likely to report a desire to avoid complications. The 72 women who achieved all stated goals reported significantly higher mean satisfaction scores than the 94 women reporting that at least one goal was not achieved (p = 0.001). Goal achievement was higher among women planning cesarean than among those planning vaginal birth (52.2% versus 23.1%, p <0.001). This research furthers our understanding of women’s attitudes regarding cesarean childbirth and definitions of a successful birth experience.